Strategic management practices for enhancing learning quality and numeracy in elementary schools - M. Musodik; Ngurah Ayu Nyoman; Soedjono Soedjono (Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the application of a comprehensive strategic management model in an elementary school participating in Indonesia’s Sekolah Penggerak program, with a particular focus on its conceptual contribution to understanding school-based strategic management in primary education. Drawing on Fred R. David’s strategic management framework, the research explores how the stages of strategy formulation, implementation, and evaluation are adapted and operationalised within the context of an elementary school to address challenges in learning quality and students’ numeracy skills identified in the school’s Education Report. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis involving school leaders and key stakeholders. The findings demonstrate that the strategic management model functions not only as an administrative planning tool but also as a conceptual framework that integrates instructional improvement, data-informed decision-making, and stakeholder engagement at the elementary school level. Despite initial constraints related to vision alignment, participation, and data literacy, the structured and reflective application of the model contributed to improvements in instructional quality and numeracy-oriented practices. Conceptually, this study extends the application of strategic management theory into the domain of elementary education by illustrating how a business-derived framework can be contextualised to support school transformation and learner-centred improvement. These findings enrich the discourse on strategic management in education and offer a transferable conceptual reference for elementary schools operating in similar reform-oriented and socio-educational contexts.